ANALISIS SENTIMEN TERHADAP PENGGUNAAN APLIKASI MERDEKA MENGAJAR DI GOOGLE PLAY STORE - Farhan, Muhammad; Ramayuda, Muhammad Davin; Ruldeviyani, Yova (J-Icon : Jurnal Komputer dan Informatika, 2024)
To provide a solution to the learning loss that has occurred in the education sector in Indonesia since the COVID-19 pandemic, the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) released the "Merdeka" curriculum. To assist teachers in obtaining references, inspiration, and understanding of the "Merdeka" curriculum, Kemendikbudristek launched the "Merdeka Mengajar" platform, which can be downloaded from the Google Play Store. However, the utilization of this application has not yet reached the target number of users expected. To determine the achieved number of users, the analysis process stages are carried out, namely data collection, data pre-processing (pre-processing), data labeling (labeling), word extraction, classification, classification evaluation, sentiment analysis using the naïve Bayes model, and Support Vector Machine (SVM). The research results, using n-gram implementation with the naive Bayes and SVM models, show that the accuracy level generated by each model is 86% and 91%, respectively. Sentiment analysis indicates that 3,225 (57%) user reviews are positive, while 2,421 (43%) are negative. Overall, it can be concluded that the sentiment regarding the use of the independent teaching application is positive. Meanwhile, several factors causing users to provide negative reviews include difficulties during activation, incomplete learning modules, and requests to release the application on IOS.